2021
DOI: 10.3389/fpubh.2021.699710
|View full text |Cite
|
Sign up to set email alerts
|

Whether Urbanization Has Intensified the Spread of Infectious Diseases—Renewed Question by the COVID-19 Pandemic

Abstract: The outbreak of the COVID-19 epidemic has triggered adiscussion of the relationship between urbanization and the spread of infectious diseases. Namely, whether urbanization will exacerbate the spread of infectious diseases. Based on 31 provincial data from 2002 to 2018 in China, the impact of urbanization on the spread of infectious diseases from the dimensions of “population” and “land” is analyzed in this paper by using the GMM (generalized method of moments) model. The empirical study shows that the populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Thus, those findings may also be applied to the scenarios of COVID-19 outbreaks in China's urban areas to some extent. In Yu's et al (1) study, population urbanization is determined by the proportion of the urban population, while the density of urban buildings measures land urbanization. Such consideration may not fully reflect the actual level and degree of the two types of urbanization.…”
Section: A Commentary Onmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, those findings may also be applied to the scenarios of COVID-19 outbreaks in China's urban areas to some extent. In Yu's et al (1) study, population urbanization is determined by the proportion of the urban population, while the density of urban buildings measures land urbanization. Such consideration may not fully reflect the actual level and degree of the two types of urbanization.…”
Section: A Commentary Onmentioning
confidence: 99%
“…Since most populations live in the cities, research in public health and urban studies regarding pandemic prevention and control in higher-density areas has become one of the top priorities in this new pandemic era. Studies revealed that population urbanization-introduced density growth does not increase the spread of infectious disease, while land urbanization-introduced building density growth can increase the risks of spreading infectious diseases ( 1 ). Moreover, regional heterogeneity is found in the distribution of impacts of urbanization on the spread of infectious diseases (ibid).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The most important aspects of urbanization are population and land ( 11 , 12 ). The urban population–land spatial patterns (UPLSPs) is the form of spatial agglomeration of urbanization elements.…”
Section: Introductionmentioning
confidence: 99%